2014
DOI: 10.1007/s10552-014-0442-y
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group and esophageal carcinoma risk: from a case–control study in Chinese population to meta-analysis

Abstract: Results from our case-control study and the followed meta-analysis confirmed that there was an increased risk of EC in blood group B individuals, whereas a decreased risk of EC was observed in blood group O individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Many reports have shown that the ABO blood type system is associated with the development of cancers. Type A has been associated with gastric [ 13 15 ], pancreatic [ 16 19 ], ovarian [ 16 , 20 ], esophageal [ 21 ], salivary gland [ 21 ], and breast cancers [ 16 ], whereas type B has been associated with esophageal [ 22 , 23 ] and laryngeal cancers [ 21 ]. Some reports showed that people with blood type O have lower risks for lung [ 24 ], endometrial [ 25 ], pancreatic [ 26 ], renal cell [ 27 ], and ovarian cancers [ 28 ], and colorectal adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that the ABO blood type system is associated with the development of cancers. Type A has been associated with gastric [ 13 15 ], pancreatic [ 16 19 ], ovarian [ 16 , 20 ], esophageal [ 21 ], salivary gland [ 21 ], and breast cancers [ 16 ], whereas type B has been associated with esophageal [ 22 , 23 ] and laryngeal cancers [ 21 ]. Some reports showed that people with blood type O have lower risks for lung [ 24 ], endometrial [ 25 ], pancreatic [ 26 ], renal cell [ 27 ], and ovarian cancers [ 28 ], and colorectal adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the most widely investigated erythrocyte antigen system and straightforward accessible element in an individual's genetic makeup ( Mao et al, 2019 ), ABO blood group system is used in clinical practice extensively ( Wang et al, 2014 ; Cooling, 2015 ). After ABO blood group system was found by Karl Landsteiner in 1901, we never interrupted searching for the relationship between ABO blood group system and various diseases ( Lesky, 1973 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ABO blood group system, the most extensively investigated erythrocyte antigen system,3 is widely used in clinical practice, and influences the host susceptibility 4 5. As an easily accessible factor in an individual’s genetic makeup, ABO blood groups have been statistically and biologically associated with many chronic diseases such as vascular disease,6 coronary heart disease7 and tumorigenesis 3 4 8.…”
Section: Introductionmentioning
confidence: 99%
“…The ABO blood group system, the most extensively investigated erythrocyte antigen system,3 is widely used in clinical practice, and influences the host susceptibility 4 5. As an easily accessible factor in an individual’s genetic makeup, ABO blood groups have been statistically and biologically associated with many chronic diseases such as vascular disease,6 coronary heart disease7 and tumorigenesis 3 4 8. For instance, by expressing on N-glycans of von Willebrand factor (VWF), ABH antigens (H antigen is the biosynthetic precursor to A and B antigens)5 impact the half-life of VWF, so VWF survival in O subjects is significantly shorter versus in non-O subjects 9–11.…”
Section: Introductionmentioning
confidence: 99%